Formation of electron radiation belts at Saturn by Z-mode wave acceleration. Issue 1 (December 2018) - Woodfield, E.; Horne, R.; Glauert, S.; Menietti, J.; Shprits, Y.; Kurth, W.
Abstract At Saturn electrons are trapped in the planet's magnetic field and accelerated to relativistic energies to form the radiation belts, but how this dramatic increase in electron energy occurs is still unknown. Until now the mechanism of radial diffusion has been assumed but we show here that in-situ acceleration through wave particle interactions, which initial studies dismissed as ineffectual at Saturn, is in fact a vital part of the energetic particle dynamics there. We present evidence from numerical simulations based on Cassini spacecraft data that a particular plasma wave, known as Z-mode, accelerates electrons to MeV energies inside 4 RS (1 RS  = 60, 330 km) through a Doppler shifted cyclotron resonant interaction. Our results show that the Z-mode waves observed are not oblique as previously assumed and are much better accelerators than O-mode waves, resulting in an electron energy spectrum that closely approaches observed values without any transport effects included. Radial diffusion is the only mechanism considered to accelerate trapped electrons to relativistic energies in Saturn's magnetic field, forming radiation belts. Here the authors show another mechanism, electron acceleration via Doppler shifted cyclotron resonant interaction with Z-mode waves, which can form radiation belts inside the orbit of Enceladus.